Experiencing fertility preservation in adolescence – a qualitative interview study indicating gender disparities in AYAs diagnosed with cancer - Rodriguez-Wallberg, Kenny A.; Nilsson, Hanna; Folmerz, Maria; Lundqvist, Erica; Granberg, Lisa; Armuand, Gabriela (Frontiers in Oncology, 2025)
IntroductionFertility counselling on options for fertility preservation is increasingly implemented for children and adolescents at time of cancer diagnosis. Sperm cryopreservation has been standard of care for male patients during several decades and the procedure is not expected to delay the onset of cancer treatment. However, oocyte cryopreservation in female adolescents remains controversial, the reasons include the need of ovarian stimulation, gynecological exams and interventions, in all a potentially distressing experience for patients without previous experience of this type of examination or without previous sexual debut. With this study we wished to investigate how adolescent cancer patients experience fertility preservation procedures aiming at semen banking or oocyte cryopreservation.MethodsAdolescent patients diagnosed with cancer that underwent fertility preservation at the Reproductive Medicine Clinic of Karolinska University Hospital were invited to participate in the study. Inclusion required the ability to communicate in Swedish or English. Exclusion criteria were current age under 15 at time of the interview and ongoing cancer treatment. The study had a qualitative study design and phenomenological approach with semi-structured individual face-to-face interviews. Ten interviews with six female and four male study participants were conducted between June and August 2023.ResultsThe analysis resulted in three identified main themes: Communication about the risk of infertility and the fertility preservation, Freezing gametes - the process and healthcare encounters, and The decision to preserve gametes for one’s own sake. Gender specific gaps in communication about fertility risks and fertility preservation procedures were found, with young females expressing a wish for improved communication and reporting experiences of discomfort during the procedures needed for oocyte cryopreservation, whereas young men were generally satisfied with their experience. Limitations include a risk of responder bias since not all patients who were contacted agreed to interview.DiscussionAlthough gender disparities were identified in this study, fertility preservation was perceived as a positive experience and mitigated fertility-related distress in both male and female adolescent patients. Our study adds to the scarce literature on adolescents of both sexes undergoing fertility preservation and underscores the importance of specialized communication in fertility counselling and treatment of AYAs diagnosed with cancer.